Correlative Evaluation of Transabdominal Ultrasonography and Magnetic Resonance Cholangiopancreatography Findings in Patients with Periampullary and Biliary System Pathologies - Sharma, Shivam; Pimpalwar, Yayati; Kumar Srivastava, Saurabh; Kumar, Ganesh; Rehbar, Nisha; Sharma, Ankit (Journal of Neonatal Surgery, 2025)
Background: Periampullary and biliary pathologies are common causes of obstructive jaundice, requiring timely and accurate imaging for effective diagnosis and management. Transabdominal ultrasonography (USG) is widely available and cost-effective, while magnetic resonance cholangiopancreatography (MRCP) provides superior anatomical visualization of the biliary system. Objective: To compare the diagnostic accuracy of USG and MRCP in detecting periampullary and biliary pathologies, using endoscopic retrograde cholangiopancreatography (ERCP) as the reference standard. Materials and Methods: This prospective observational study was conducted over 18 months (May 2023 to November 2024) in the Department of Radiodiagnosis at the Integral Institute of Medical Sciences and Research, Lucknow. A total of 45 patients with clinical and laboratory evidence of obstructive jaundice were enrolled. All patients underwent USG followed by MRCP. Imaging findings were assessed for choledocholithiasis, common bile duct (CBD) dilatation or obstruction, gallbladder pathology, and periampullary lesions. ERCP findings served as the gold standard. Diagnostic performance parameters, including sensitivity, specificity, accuracy, and positive predictive value (PPV), were calculated using SPSS v20.0. Results: MRCP identified all 17 cases of choledocholithiasis confirmed by ERCP, whereas USG missed three distal CBD stones. MRCP also detected more biliary and periampullary malignancies. USG showed 77.5% sensitivity, 60% specificity, 75.6% accuracy, and 93.9% PPV. MRCP showed superior performance: 92.5% sensitivity, 80% specificity, 91.1% accuracy, and 97.4% PPV. Conclusion: USG remains a valuable first-line screening modality for evaluating biliary obstruction due to its accessibility and cost-effectiveness. However, MRCP offers significantly greater diagnostic accuracy, especially in detecting distal CBD stones and periampullary malignancies. Owing to its non-invasive nature and high diagnostic yield, MRCP serves as a reliable alternative to ERCP in the preoperative evaluation of obstructive jaundice.